ISLANDERS FROM PAULISTA NORTH COAST – SPACE, FISHING AND WORK - Cardoso, Eduardo Schiavone; Thomaz Junior, Antonio (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2013)
The article shows a concern for establishing the connections among the fishing activity, considered as a labor activity, the discussions that there are in the dynamics from the world of work in contemporary and changes in geographical space, considering as study focus the insular spaces inhabited by islanders in paulista north coast, in special, Vitoria and Monte de Trigo islands. Based on the process of the coast space occupation and the configuration of fishing setting in Brazil, the research sought to analyze socio-economical and space changes occurred in the islands mentioned, in the last two decades. It was identified the new problems presented for the islanders and their strategies of economic and social reproduction, regarding the occupation process of paulista north coast, which is characterized by increased urbanization, expansion of coastal and marine tourism, expansion of energetic setting in the region, among other spatial dynamics.